2006
DOI: 10.1038/sj.cdd.4401967
|View full text |Cite
|
Sign up to set email alerts
|

Increased apoptosis, huntingtin inclusions and altered differentiation in muscle cell cultures from Huntington's disease subjects

Abstract: Mutated huntingtin (htt) is ubiquitously expressed in tissues of Huntington's disease (HD) patients. In the brain, the mutated protein leads to neuronal cell dysfunction and death, associated with formation of htt-positive inclusions. Given increasing evidence of abnormalities in HD skeletal muscle, we extensively analyzed primary muscle cell cultures from seven HD subjects (including two unaffected mutation carriers). Myoblasts from presymptomatic and symptomatic HD subjects showed cellular abnormalities in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
75
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 41 publications
(48 reference statements)
5
75
0
1
Order By: Relevance
“…In a recent publication referring to human primary muscle cultures from Huntington disease (HD) patients, similar vacuoles were described in HD cultures but not in controls. 17 As in our cultures, these structures were not visible in myotubes. We suggest that this phenomenon is not an in vitro manifestation of HIBM pathological processes, but a possible characteristic of the normal growth of cultured adult skeletal muscle cells.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…In a recent publication referring to human primary muscle cultures from Huntington disease (HD) patients, similar vacuoles were described in HD cultures but not in controls. 17 As in our cultures, these structures were not visible in myotubes. We suggest that this phenomenon is not an in vitro manifestation of HIBM pathological processes, but a possible characteristic of the normal growth of cultured adult skeletal muscle cells.…”
Section: Discussionsupporting
confidence: 51%
“…The changes in apoptotic processes seen in HIBM satellite cells might be one of the initial pathologic events leading to the degeneration of muscle tissue, since they appear during the mitotic phase, while other biological functions of the cells -morphology, proliferation, senescence and differentiation -seem normal. In contrast, in highly degenerative diseases such as HD, CMD and DMD, most basic biological functions are impaired from the early stages of satellite cells activation, 17,19,21 and therefore even when apoptotic processes are involved, it is difficult to point to the initial steps of the process. Presently, the upstream events in HIBM pathophysiology, in terms of intracellular and intercellular signaling, have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…HD subjects also showed a deficit in mitochondrial oxidative metabolism in skeletal muscles, as judged by a significant decrease in phosphocreatine recovery after exercise [40]. Additionally, in vitro muscle cell cultures exhibited abnormalities in mitochondrial membrane potential and cytochrome 3 release [41].…”
Section: Discussionmentioning
confidence: 99%
“…In peripheral tissues, mutant huntingtin was reported to affect the activity of mitochondrial complex I (Arenas et al, 1998) and complexes II-III (Ciammola et al, 2006;Turner et al, 2007) along with mitochondrial depolarization, cytochrome c release and increased caspases activity (Ciammola et al, 2006;Turner et al, 2007) in skeletal muscle. In platelets from HD patients, some authors found a decrease in complex I activity (Parker et al, 1990), whereas others reported no changes in the activity of mitochondrial complexes (Gu et al, 1996;Powers et al, 2007a).…”
Section: Introductionmentioning
confidence: 99%